The remarkable role of rosemary officinalis & Tamarix Aphylla against radiation based therapy - SOHAIR ALY HASSAN; EL SHERBINY M; AMANI N. HASHIM (International Journal of Pharma and Bio Sciences, 2017)
Rosmarinus officinalis L and Tamarixaphylla are among herbal plants known in the Mediterranean region, with a long history of medicinal and culinary use. These plants are rich source of antioxidants which mainly attributed to its components. The modifying influence of leaves extract of both Rosmarinus officinalis (rosemary) and Tamarixaphylla (Athel) against irradiation intoxication were investigated in experimental albino rats. Selected doses were chosen as radio protectors against Gamma [γ] radiation hazards. The experimental Westar rats were exposed to 5 Gry for 15 min before and after treatment with rosemary and tamarix extracts in a dose of 100 mg/kg/ b/ wt of each respectively. The treated animals were autopsied for collection of blood serum at days 1, and 15 post-irradiation. A decrease in the hematological parameters and Glutathione level was registered in the positive irradiated control group. A recovery pattern were recorded in the pre and after treated groups. The whole hematological parameters were ameliorated back to the normal by day 15; as a significant elevation was achieved with groups treated with rosemary and tamarix extracts compared to irradiated one. An increment in the level of lipid peroxidation above normal was noted in serum of irradiated rats. This increment was significantly reversed upon treatment by rosemary and tamarix extracts. Moreover interlukin 6 levels were highly modified in the treated groups. The whole results were confirmed Histologically by the improvement seen in the (PCNA) ( proliferating cell nuclear antigen )level antigen. Considering these biochemical and histological results, the present study suggests the significant importance for both herbs with the superior role of rose marry as a magnificent radio modifier herb.